KENDALA-KENDALA YANG DIHADAPI GURU SMK NEGERI 5 PADANG DALAM MELAKSANAKAN 4 TAHAP PENELITIAN TINDAKAN KELAS - 888-909 , Aida Rasita (Universitas Negeri Padang, 2016)
ABSTRACT The aim of this research to reveal the constraints experienced teachers of SMK Negeri 5 Padang in implementing PTK 4 stages in the semester from July to December 2015. This research is descriptive quantitative and technique of sampling using Proportional Random Sampling 58 of 139 people population. Data were collected using a questionnaire with Likert scale consisting of four possible answers. The number of items in the questionnaire research as much as 39 point statement.The results showed that the constraints faced by Guru SMK 5 Padang In Implementing TOD namely: the indicator (1) Planning action research experience problems with an average degree of achievement of 74.57% are sufficient. (2) The act of classroom action research experience problems with an average degree of achievement of 82.76% including the big categories. (3) Observation of classroom action research experience problems with an average degree of achievement of 73.11% are sufficient. (4) Reflection classroom action research experience problems with an average degree of achievement of 70.85% are sufficient.Keyword: Teacher of SMK N 5 Padang, Class Action Research